PENGARUH PBV, EPS, DAN DER TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING : STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009-2013 - IRENE NATHASIA DEVI; SUTRISNO T (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purpose of this research is to examine the effect of Price Book Value (PBV), Earning Per Share (EPS), and Debt to Equity Ratio (DER) either directly or indirectly on stock price with used dividend policy as an intervening variable. Dividend Payout Ratio (DPR) used as a proxy of dividend policy. The sample used in this study consisted of 32 manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2013, 160 the number of observations. Sampling was done by purposive sampling methode. This research used is path analysis to quantify the direct and indirect effect of each variable on stock prices. The result of the analysis show that have positive to dividend policy, but EPS and DER have negative to dividend policy. Dividend policy have positive to stock price. PBV and EPS have positive to stock price, DER have negative to dividend policy. Based on result indirect analysis show that have PBV, EPS, and DER to stock price can mediated using dividend policy. Keywords: Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR), Earning Per Share (EPS), Price Book Value (PBV), and Stock Price.